Pemberdayaan Siswa SMA Negeri 1 Unaaha melalui Pelatihan Laboratorium Virtual Berbasis PhET - La Sahara; Waode Alkamalia (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to introduce the use of the PhET virtual laboratory and to identify students’ responses to the PhET-based virtual laboratory training in empowering students at SMA Negeri 1 Unaaha. The program also seeks to address the issue of limited science practicum facilities in the partner school. The study employed a descriptive quantitative design involving a single group of 23 participants from grades X to XII in the science stream. Participants took part in several sessions, including orientation, demonstration, and exploration of the Build an Atom and Circuit Construction Kit: DC simulations. Research data were collected using a Likert-scale questionnaire consisting of 30 items covering six main indicators: conceptual understanding, motivation, activeness, interest, ability to operate PhET, and learning satisfaction. All questionnaire results were converted into percentages for each indicator. The analysis showed an average response rate of 86.67%, with details as follows: interest 92%, activeness 90%, motivation 88%, satisfaction 89%, operational ability 83%, and conceptual understanding 78%. These findings indicate a very positive acceptance and significant reinforcement in the affective, participatory, and technical skill aspects of the students.